Costo/efficacia della prevenzione di infezioni alle prime vie aeree mediante un estratto batterico immunostimolante aspecifico (OM-85) - Zaniolo, Orietta; Pradelli, Lorenzo; Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2005)
OBJECTIVES: To estimate the pharmacoeconomical impact of preventing recurrent upper respiratory tract infections (URTIs) with OM-85, a non-specific immunostimulating agent, in at-risk children. METHODS: Implementation of a decisional model. The evaluation of effectiveness (number of prevented URTIs/therapeutic cycle) was based on weighted average of the results of four randomized, double-blind, placebo-controlled trials identified by literature reviewing. The clinical events considered in the model were natural resolution of the infection, onset of complications (acute otitis media, sinusitis, others) and their evolution. Baseline event probabilities were derived by reviewing published data in the literature. URTI-related direct and indirect costs supported by patient, by Italian health system and by community were structured according with the principal guidelines and implemented with current Italian prices and tariffs. The cost/ effectiveness of OM-85 was calculated for five scenarios, differing in the number of therapeutic cycles, grade of patient co-payment and other secondary assumptions. Sensibility analyses were performed to evaluate the model robustness. RESULTS: Immunostimulation with one cycle of OM-85 prevented on average 1,60 URTI/patient in six months (RR = 0,515). In the basic scenario, this preventive action induced savings for 107,42 euro/patient in the perspective of the patient’s family, for 48,52 euro/patient in the perspective of Italian health system and for 231,26 in the community perspective. Sensibility analyses confirmed the robustness of basic scenario results. Threshold analyses showed that OM-85 prophylaxis is economically convenient as long as more than 7% of infections are prevented or global cost of one episode of URTI is greater than 10,00 euro. CONCLUSIONS: Non-specific immunotherapy with OM-85 induces a reduction in the incidence of URTIs in atrisk children with a concurrent saving for patient and health system.